Building industrial clusters in Latin America: Paddling upstream (2011)
Analysis of more than 20 projects for clustering small and medium enterprises and supporting organizations in different Latin American countries has uncovered a number of barriers, activities, structures, strategies, policies and procedures that impact competitiveness. These factors mean that there are different appropriate industrial cluster and industrial business models appropriate for the social, economic, and business conditions of the Latin American region. It is difficult to transfer successful practices from industrialized countries to developing regions with a light adaptation, because it is impossible to have 'clustering readiness' when resources are scarce, regional and industrial conditions are hostile, and associated capabilities of the participants of clustering are poor or nonexistent. These conclusions are supported by applying a methodology designed by the authors to identify global opportunities and formulate viable cluster structures, capable of converting isolated scarce resources in difficult situations, into world-class regional value propositions. Copyright © 2011, IGI Global.